"Flexible citizenship" in Chinese international secondary school students' transnational social networks: opportunities or constraints?. Issue 6 (2nd November 2021) - Wu, Xi; Zheng, Jie
ABSTRACT: Using the notion of  "flexible citizenship", this paper examines how Chinese international secondary school students accumulate and exchange different forms of capital as governed by their transnational social networks. This study draws on data from a 14-month ethnographic field study on the transnational lives of 11 Chinese students in a Canadian international secondary school. This study illustrates that the instrumental dimension of "flexible citizenship" produced both opportunities and tensions in student participants' lives when their new and existing social relations converged to mediate their transnational lives and trajectories. The force of multiple transnational actors to maximise opportunities exerted emotional pressures on students and caused relational tensions. In addition, when the participating students encountered challenges in broadening social connections in the host society, they solidified home social connections for emotional support and further academic and career development, although such practices constrained their effort in intercultural learning for embodied cultural capital. This paper advocates that beyond the governmental logic of instrumental "flexible citizenship", all social actors should gain more nuanced and comprehensive understanding of students' lives and their relational and emotional development. Additionally, Chinese students may be given more freedom in enacting their agency to engage with their transnational and intercultural lives in the ways they desire rather than those that are desired by external social forces.